Workplace motivation: amongst positive circle / Mohd Nur Fitri Mohd Salim ... [et al.] - Mohd Salim, Mohd Nur Fitri; Mohamad Yusuf, Asmahanim; Mohd Salim, Mohhamad Safwat Ashahri; Mohd Nasir, Muhammad Zulqarnain; Sapini, Muhamad Luqman (Universiti Teknologi MARA, Negeri Sembilan, 2023)
As people, our minds are heavily influenced by our surroundings. This is particularly crucial, especially in a workplace environment where the need to create a conducive environment is a necessity in meeting the demand of tasks and goals set by the institution. Significant increases in energy, happiness and initiative are among the results of a positive mind created by positive surroundings. As an institution strives for success, emphasis on building an encouraging workplace surrounding needs to be nurtured along the efforts in achieving its visions and missions. Simon Sinek, a prominent author and motivational speaker, expressed that individuals who are emotionally invested are more focused on making a positive impact rather than seeking personal gain. Therefore, the relevance of choosing or creating a positive community in a workplace setting should not be underestimated in the workplace environment as various studies indicate the influence of a positive work atmosphere in producing increased productivity, commitment and achievement-striving ability amongst co-workers (Zhenjing et al., 2022).